The role of primary antifungal prophylaxis in patients with haematological malignancies. (3rd February 2014) - Pagano, L.; Caira, M.
Abstract: Invasive fungal infections (IFIs) represent important complications in patients with haematological malignancies. Chemoprevention of IFIs may play an important role in this setting, but in the past decades the majority of antifungal drugs utilized demonstrated poor efficacy, particularly in the prevention of invasive aspergillosis. The new triazoles are very useful antifungal drugs, more suitable for prophylaxis of IFIs than amphotericin B and echinocandins. In this review, the main clinical data about antifungal prophylaxis with fluconazole, itraconazole, voriconazole and posaconazole are analysed. At present, posaconazole appears to be the most efficacious azole in antifungal prophylaxis, particularly in patients with acute myeloid leukaemia.